Enhancement of Fenton processes at initial circumneutral pH for the degradation of norfloxacin with Fe@Fe2O3 core-shell nanomaterials. Issue 27 (6th December 2019) - Liu, Jingyi; Hu, Wenyong; Sun, Maogui; Xiong, Ouyang; Yu, Haibin; Feng, Haopeng; Wu, Xuan; Tang, Lin; Zhou, Yaoyu
ABSTRACT: The degradation of norfloxacin by Fenton reagent with core-shell Fe@Fe2 O3 nanomaterials was studied under neutral conditions in a closed batch system. Norfloxacin was significantly degraded (90%) in the Fenton system with Fe@Fe2 O3 in 30 min at the initial pH 7.0, but slightly degraded in Fenton system without Fe@Fe2 O3 under the same experimental conditions. The intermediate products were investigated by gas chromatography-mass spectrometry, and the possible Fenton oxidation pathway of norfloxacin in the presence of Fe@Fe2 O3 nanowires was proposed. Electron spin resonance spectroscopy was used to identify and characterize the free radicals generated, and the mechanism for norfloxacin degradation was also revealed. Finally, the reusability and the stability of Fe@Fe2 O3 nanomaterials were studied using x-ray diffraction and scanning electron microscope, which indicated that Fe@Fe2 O3 is a stable catalyst and can be used repetitively in environmental pollution control. GRAPHICAL ABSTRACT: